2022
DOI: 10.3897/phytokeys.210.87033
|View full text |Cite
|
Sign up to set email alerts
|

Liparis macrosepala (Orchidaceae), a new species from southwest China with its phylogenetic position

Abstract: A new orchid species, Liparis macrosepala, is illustrated and described from Yunnan Province, China, based on morphological and molecular analyses. This plant is characterised by the ovoid-fusiform, slightly compressed pseudobulbs with 4 or 5 leaves with slightly crisped margins on their apical half, dorsal sepal heart-shaped, lip with a bituberculate basal callus and a thickened folded lateral lobe on each side, centrally with one cavity with slightly raised margins, the column with a single pair of broadly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…consists of about 320 epiphytic and geophytic species and is widely distributed in tropical, subtropical, and temperate regions of the Old and New Worlds, being distinguished from other members of Malaxidinae mainly by the elongate column with an apical, incumbent anther ( Ridley 1886 ; Cribb et al 2005 ). Although several molecular phylogenetic studies have shown that Liparis is polyphyletic ( Cameron 2005 ; Tang et al 2015 ; Li et al 2020 ; Ya et al 2021 ; Wang et al 2022 ), such studies have been strongly biased towards tropical/subtropical Asian taxa. Many Neotropical species have not yet been included in molecular analyses, and much work remains to be done to attain a clear picture of generic limits and relationships in this region.…”
Section: Introductionmentioning
confidence: 99%
“…consists of about 320 epiphytic and geophytic species and is widely distributed in tropical, subtropical, and temperate regions of the Old and New Worlds, being distinguished from other members of Malaxidinae mainly by the elongate column with an apical, incumbent anther ( Ridley 1886 ; Cribb et al 2005 ). Although several molecular phylogenetic studies have shown that Liparis is polyphyletic ( Cameron 2005 ; Tang et al 2015 ; Li et al 2020 ; Ya et al 2021 ; Wang et al 2022 ), such studies have been strongly biased towards tropical/subtropical Asian taxa. Many Neotropical species have not yet been included in molecular analyses, and much work remains to be done to attain a clear picture of generic limits and relationships in this region.…”
Section: Introductionmentioning
confidence: 99%